Determinants of SOE's performance: A systematic literature review - Muhammad Alam Mauludina; Yudi Azis; Citra Sukmadilaga; Hendra Susanto (Cogent Business & Management, 2023)
The objective of this study is to conduct a systematic review of the factors influencing the profitability performance of State-Owned Enterprises (SOEs). To achieve this objective, a qualitative method was employed, utilizing the Systematic Literature Review (SLR) approach to collect relevant data. A total of 328 published empirical articles were selected from the Scopus database and various journals, which served as the sample. This study presents an extensive examination of the literature on the trend of SOE profitability performance and its influencing factors. The obtained result showed that there was a notable increase in the number of articles published on this topic, particularly after 2015, with the highest number of publications occurring in 2022. It is important to note that the majority of these articles were predominantly published in China which aligned with the significant presence of SOE in the country. Most of the analyzed papers utilized quantitative methods and employed panel regression as the statistical tool for their data analysis. Furthermore, it was observed that corporate governance emerged as the most commonly studied independent variable in these articles. This study also offers insight into areas that warrants further investigation in terms of what has been examined and what is yet to be. Lastly, the study contributes to determining the overview of the state of the art of SOE performance and provides a knowledge gap for further analysis.
Keywords: 650; corporate governance; firm performance; profitability; State-Owned Enterprise; Systematic Literature Review